Effectiveness of Schema Therapy on Severity of Depression and Rumination in Patients with Treatment Resistance Depression - Simin Gholamrezae (Journal of Global Pharma Technology, 2017)
Background: schema therapy is an important method in treatment of mental disorders special in treatment of depression. This study aimed to determine the effectiveness of schema therapy on severity of depression and rumination in patients with treatment resistance depression. Method: This study was a quasi-experimental with a pre-test, post-test design that 48 patients with treatment resistance depression were selected through available sampling method and randomly assigned in tow groups. The experimental group educated 12 sessions of 90 minutes by schema therapy method. Groups completed the questionnaire of Beck depression (BDI-II) ruminative response scale (RRS). Data was analyzed with using the SPSS software and by multivariate analysis of covariance (MONCOVA) method. Results: The findings showed there was a significant difference between schema therapy and control group on severity of depression and rumination (P<0.05). Conclusion: Therefore, counselors and therapists can use schema therapy for decreasing symptoms of depression disorder and rumination.Keywords: Schema therapy, Severity of depression, Rumination, Treatment resistance depression.